Deaf interpreters’ roles and its problematizing in regular schools - Romário, Lucas (2021)
As result of a doctoral dissertation research about Education, this article problematization focuses on the way of incorporation of deaf people’s work as interpreters in Regular Schools of João Pessoa, Paraíba, Brazil. The qualitative research was anchored on theorical Deaf Studies considering the Cultural Education Studies area, also developed with deaf professionals from seven public schools. The intreview analysis showed that deaf people did not have official formation in the area of translation/interpretation – their salaries were inappropriate even if some of them had a higher education, so they received high school salaries, and the central point was that the conditions of linguistic use of their work were questionable, considering that the translation /interpretation should be performed from oral to sign language and vice versa (intermodal translation).